Sinergi bio-surya: Model kemitraan pengabdian masyarakat untuk transformasi limbah dapur menuju kemandirian energi - Gema Romadhona; Rum Sapundani; Itmi Hidayat Kurniawan; Tanziila Faidza Arfa; Anggito Imam Raharjo (Nur Science Institute, 2026)
RW 06 in Purwosari Village, Baturraden Subdistrict, faces two major challenges: unmanaged daily kitchen waste that contributes to sanitation and environmental problems, and reliance on PLN electricity, which is unreliable and costly for communal needs. This article presents the design, implementation, and effectiveness of the